Factors influencing success of new product launch: a case of SME stationery industry in India - B, Haresh; Suresh, M; Ranganathan, Rajkumar (International Journal of Engineering and Technology, 2018)
Launching a new product in market always holds a lot of challenges; which are even magnified when it is an SME that is launching the new product. The objective of this paper is to identify how the different factors that influencing success of new product launch interact and im-pact each other in SMEâ€™s of stationery industry in Tamil Nadu, India. Interpretive structural modelling(ISM) approach is used to analyse interrelationship between the factors. MICMAC analysis is performed to categorise and rank the factors according to their importance and function. Finally, the paper concludes with most influential factorsare core competence and manufacturing flexibility for the new product launch of stationery industry.Â